2009 IEEE Symposium on Visual Analytics Science and Technology 2009
DOI: 10.1109/vast.2009.5333245
|View full text |Cite
|
Sign up to set email alerts
|

VAST contest dataset use in education

Abstract: The IEEE Visual Analytics Science and Technology (VAST) Symposium has held a contest each year since its inception in 2006. These events are designed to provide visual analytics researchers and developers with analytic challenges similar to those encountered by professional information analysts. The VAST contest has had an extended life outside of the symposium, however, as materials are being used in universities and other educational settings, either to help teachers of visual analyticsrelated classes or for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…The contest datasets have been used in class projects 13 and lend themselves for evaluation studies since answers can be easily graded because of the embedded ground truth. However, the contest datasets are too large and too complex to be used in lab experiments for formal evaluations of visual analytics systems.…”
Section: Using Contest Datasets For Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The contest datasets have been used in class projects 13 and lend themselves for evaluation studies since answers can be easily graded because of the embedded ground truth. However, the contest datasets are too large and too complex to be used in lab experiments for formal evaluations of visual analytics systems.…”
Section: Using Contest Datasets For Evaluationmentioning
confidence: 99%
“…Our analysis activities in the VAST Contest/ Challenges using the large examples with embedded ground truth exposed a number of shortcomings in the Jigsaw system, and thus, the activities functioned very much in a formative evaluation sense. The contest datasets have been used in class projects 13 and lend themselves for evaluation studies since answers can be easily graded because of the embedded ground truth. However, the contest datasets are too large and too complex to be used in lab experiments for formal evaluations of visual analytics systems.…”
Section: Using Contest Datasets For Evaluationmentioning
confidence: 99%
“…We also collected feedback from users through email, which confirmed that datasets are often used to teach classes [18] and various other purposes. We asked eleven questions about the VAST Challenge and its impact on their goals for their research.…”
Section: Surveysmentioning
confidence: 83%
“…Moreover, the use of datasets and problems is expanding into the educational realm. 29 The enduring central presence of the VAST Challenge at the conference, the sustained rate of participation and dataset downloads, and the participant survey results indicate continuing interest from the researchers and practitioners and suggests that the Challenge is contributing to the overall evaluation of visual analytics systems. Evaluating accuracy remains the main challenge as we move toward more realistic scenarios and data.…”
Section: Resultsmentioning
confidence: 98%